Highly efficient microfluidic sorting device for synchronizing developmental stages of C. elegans based on deflecting electrotaxis1. Issue 11 (7th June 2015) - Wang, Xixian; Hu, Rui; Ge, Anle; Hu, Liang; Wang, Shanshan; Feng, Xiaojun; Du, Wei; Liu, Bi-Feng
<x xml:space="preserve">Abstract</x> We propose a PDMS–agarose hybrid microfluidic chip for simultaneous sorting of all the different stages of C. elegans.